2017
DOI: 10.1002/esp.4184
|View full text |Cite
|
Sign up to set email alerts
|

A study of a flowslide with significant entrainment in loess areas in China

Abstract: Flowslides are a frequent type of natural disaster in loess areas and may result in the significant loss of properties and/or casualties. The Dagou flowslide is a typical event in a loess area and is accompanied by significant sediment entrainment. To analyze the mechanisms responsible for flowslides and to obtain the parameters for a runout analysis, a field investigation was conducted. Specimens were sampled on site to carry out laboratory tests, including a triaxial test, sieve analysis, and chemical compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Loess is characterized by looseness, porosity, and easy water seepage. It is easily eroded by flowing water to form gullies, which can easily cause subsidence and collapse [1][2][3][4]. Loess is widely distributed in Northwestern China, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Loess is characterized by looseness, porosity, and easy water seepage. It is easily eroded by flowing water to form gullies, which can easily cause subsidence and collapse [1][2][3][4]. Loess is widely distributed in Northwestern China, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Loess has long been studied because of its collapsible mechanical properties. It is commonly reported that loess suffers a great loss of strength when subjected to wetting, for example after rainfall or irrigation, (Derbyshire et al, 1994;Muñoz-Castelblanco et al, 2011;Jiang et al, 2012;Zhang et al, 2017), and this property is believed to be the main reason for the frequently occurring collapse of shallow loess slopes (Zhang et al, 2009;Xu et al, 2011;Xu et al, 2014;Leng et al, 2018). Deeper failures have also been observed, sometimes in the form of landslides, but they are less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Landslide has become the most damaging environmental hazard [1][2][3][4][5][6], and the main triggering factors of this hazard are rainfall [7][8][9][10][11][12][13] and earthquakes [14][15][16]. A problem in the analysis of water-related landslide is the lack of data on rainfall-triggered landslide (RTL).…”
Section: Introductionmentioning
confidence: 99%